Penerapan Metode Talaqqi Dalam Meningkatkan Hafalah Al Qur’an di Sekolah Menengah Pertama Islam Terpadu Mardhatillah Tahun Pelajaran 2023/2024 - Faththur Rohmaman Imam Fakhih Irsyady Romadhan; Isfihani Isfihani; Praptiningsih Praptiningsih (Departement of Mathematics Education, 2023)
In every time memorizing the Qur'an, everyone has different difficulties whether it is from their children who cannot read the Qur'an or children who are able to read the Qur'an but are still stammering in reading it, therefore a method is needed that can facilitate students in memorizing the verses of the Qur'an. The method is a tool used to facilitate student memorization, one of which is the Talaqqi method, this method is very important in achieving success in memorizing the Qur'an. Because, the success and failure of a goal is determined by the method, which is an integral part of the learning system. One method that can improve the quality of memorization is the Talaqqi method, what is meant by the Talaqqi method is the meeting of teachers and students in a halaqah then students deposit or listen to the memorization that has just been memorized to the teacher or Ustadzah. The Talaqqi process is carried out to find out the results of a prospective Hafidz's memorization and get guidance as needed. The implementation of the Talaqqi method has an impact on the quality of student memorization in terms of the amount of memorization or in terms of reading. There are several ways that the ustadz or ustadzah can improve memorization of the Qur'an. Where the Talaqqi method has the characteristic of meeting directly with the ustadz or ustadzah in learning and memorizing. Meanwhile, the presence of an ustadz or ustadzah in memorizing the Qur'an plays an important role in bringing students to the correct memorization. Which in this study aims to determine the application of the Talaqqi method at SMPIT Mardhatillah Sukoharjo. The study used a descriptive qualitative approach, to obtain information from ustadz or ustadzah and from students using observation, interview and documentation methods.